Optical fiber sensors for measurements in life sciences (2018)
The fiber optic communications industry has undoubtedly revolutionized the information and telecommunications technology (ICT) offering higher-performance and more reliable telecommunication links with ever decreasing bandwidth cost [1]. Simultaneously with these developments, fiber optic sensor technology has been associated with the optoelectronic and fiber optic communications industry, and many of the components associated with these industries were often developed for fiber optic sensor applications [1]. Fiber optic sensors take advantages of the exceptional characteristics of the optical fiber, which include compactness and small size, fast response, high resolution and sensitivity, good stability and repeatability, multiplexing capabilities, remote sensing, high flexibility, low propagating loss, affordable fabrication costs, simultaneous sensing ability, and resistance to electromagnetic interference [2–5] [1]. As optics and fiber optics component prices have fallen and quality has improved, the competence of fiber optic sensors to displace traditional sensors has increased [1], [6]. Nowadays, sensors rule the world. Sensors play a fundamental role to control and predict different products and systems, from consumer electronics to industrial environments, passing by the weather monitoring and biological and healthcare diagnosis. Those applied to health care monitoring have many benefits: minimize the cost per analysis, easy access to remote places without laboratory facilities such as vulnerable populations, reduce the treatment time and optimize the resources of the government health care system, among others [7–10]. In Colombia, for example, some transmissible diseases most frequently affect the most vulnerable populations. Since the Ministry of Health and Social Protection in Colombia should guarantees free diagnosis and treatment, and many of Colombia’s rural areas have no access to adequate health services due to geographical and demographic 26 Optical Fiber Sensors for measurements in Life Sciences characteristics, along with the difficulties caused by the armed conflict, and other situations of violence; the priority must be given to those rural areas. One of the main purposes of the Ministry of Health and Social Protection is to carry out continuous and systematic monitoring of the epidemiological behavior in transmissible diseases. This monitoring should be performed in accordance with processes established that allow the notification, collection, and data analysis. Thus generating valid and reliable timely information to guide prevention and control measures for those diseases [11]. However, achieving this purpose is very complicated if conventional methods used for the detection of the diseases fail to reach the population affected. Therefore, it is essential to adapt and improve the technology used to detect those diseases when it is required to collect information at the remote zones with difficulties in accessing health services. The optical fiber biosensensing technology exhibits a good promising future to solve the issues that the conventional diagnosis methods used present such as: long procedures, expensive equipment and reagents, specialized personnel, lack of portability, low sensitivities, and need of biomarkers. In addition to the sensitivity and selectivity, one of the fundamental characteristics that makes most biosensors so potential is the possibility of performing the analysis of the substance to be determined directly, i.e. without the need for a marker, and in real time. These two characteristics give biosensors the possibility to perform not only a qualitative and quantitative analysis, but also the possibility of evaluating the kinetics of the interaction (affinity constant, association and dissociation, among others) and, therefore, elucidate the fundamental mechanisms of such interaction. In this thesis it is studied a novel biosensing technology applied to immunoassays (detection of an antigen/antibody binding) based on the single-mode-multimode-single mode (SMS) fiber optic structure. This structure consists of optical fiber that relies on a multimode interferometry operating principle. Optical fiber SMS immunosensors here studied present several advantages: Optical Fiber Sensors 27 • The proposed structure has biosensing parameters comparable to those achieved by more complex structures like long period grating and surface plasmon resonances, which places this immunosensing device as a very promising option for biological and medical applications where high sensitivities, high selectivity and compact structures are required. • The sinusoidal spectrum of the SMS sensors proposed allows a sharp peak corresponding to the fundamental frequency to be observed. Consequently, it is possible to obtain a phase sensitive device by tracking the phase of this fundamental frequency as a function of the parameter to detect. FFT analysis technique is shown to have advantages since it could simplify the detection system making unnecessary the use of sophisticated optical interrogators. • The proposed structure and the bioassay performed is a label free assay, which implies that detection molecules are not labelled or modified. This means easier and lower cost procedures. The main results obtained using this concept of biosensors will be presented along this thesis as is described. First, Chapters 1 and 2, include an overview of the optical fiber sensors field, mainly focused on optical fiber biosensors. The sensors developed as a result of this thesis are presented as contributions in Chapters 3, 4, 5 and 6. These contributions were submitted to peer-reviewed top scientific journals and conferences. Finally, Chapter 7 presents and discusses a series of conclusions, current work, and future perspectives derived from this thesis.